Axial eccentric SynRel and SPM Motors analytical models validation using 3D finite element - Mahmoud, Hanafy; Al-Timimy, A.; Degano, Michele; Di Nardo, Mauro; Bianchi, Nicola; Gerada, C. (2017)
This paper deals with the uniform and non-uniform axial eccentricity analyses of the surface mounted permanent magnet and synchronous reluctance machines. The analyses are carried out using an analytical model for each considered machine. Being the axial eccentricity a 3D physical phenomenon, the standard sliding approach used in the analytical models has been validated through accurate 3D FE simulations. The results presented in this paper verify the effectiveness of the analytical approaches quantifying the results deviations respect to the computational expensive 3D FE simulations. The results also confirms that synchronous reluctance machines show higher radial forces compared to the surface permanent magnet machines for the same eccentricity level, main geometry and operating condition.